Task Control Deficit in Individuals With Non-suicidal Self-Injury - Lee, Seo Jeong; Hyun, Myoung Ho (Frontiers in Psychiatry, 2021)
Numerous people in clinical settings who have experienced repeated self-injuries explain their non-suicidal self-injury (NSSI) as “habitual” or due to “difficulty avoiding impulses related to NSSI”. Previous studies present retrospective reports, where they experience frequent self-injurious urges and try to resist but fail. However, no study has directly investigated repeated behavioral control problems of people who engage in chronic NSSI through behavioral measurements in an experimental setting. The current study sought to investigate whether people who repeatedly attempt NSSI demonstrate deficiency in task control ability called the object-interference (O-I effect). The current study performed object interference tasks on 90 participants, of which 45 were those who reported repeated NSSI while 45 comprised the control group. We observed delayed reaction times for object stimulus compared to abstract stimulus in the NSSI group, indicative of the object interference effect. This reflects task control deficits and difficulties in NSSI related behavioral control in the repeated NSSI group. When NSSI tools were additionally presented as a target stimulus, longer reaction times and more errors were observed in the NSSI group compared to the control group. The current study discusses the clinical implications of the results from diagnostic point of view and provides suggestions for future research for treatment and prevention.